ORGANIZING COST AND RESULT ACCOUNTING USING THE DIRECT COSTING SYSTEM (International journal of artificial intelligence, 2025)
This article examines direct costs and variable indirect expenses involved in calculating product cost, as well as key issues in improving cost accounting in enterprises.